A new species of Paspalum (Poaceae, Panicoideae, Paspaleae—Recta group), from the cangas of the Serra dos Carajás, Pará, Brazil - Moura, Clapton Olimpio De; Viana, Pedro Lage; Oliveira, Regina Célia (Phytotaxa, 2018)
A new species, Paspalum cangarum, morphologically similar to P. brachytrichum, is described. While both occur in canga vegetation, P. brachytrichum is endemic to the state of Minas Gerais and the new species is restricted to the Serra dos Carajás, state of Pará, Brazil. These species can be distinguished from each other mainly by their height, length and number of racemes and by the lengths of their pedicels and spikelets.